A case series study of an innovative community-based brief psychological model for men in suicidal crisis. (4th May 2022) - Chopra, J.; Hanlon, C. A.; Boland, J.; Harrison, R.; Timpson, H.; Saini, P.
Abstract: Objectives: To conduct a 1-year evaluation of James' Place, a suicidal crisis centre delivering a clinical intervention in a community setting. Design: A case series study, following men entering the service during the first year of operation. Participants: Men experiencing a suicidal crisis referred to the service ( N  = 265), with N  = 176 going on to engage in therapy. Intervention: The James' Place Model is a therapeutic intervention offered to men who are in a suicidal crisis. Trained therapists provide a range of therapeutic approaches and interventions, focusing on decreasing suicidal distress and supporting men to develop resilience and coping strategies. Main outcome measures: CORE-34 Clinical Outcome Measure (CORE-OM). Results: For all subscales of the CORE-OM there was a significant reduction in mean scores between assessment and discharge ( p  < 0.001), with all outcomes demonstrating a large effect size. All reductions illustrated a clinically significant change or a reliable change. Conclusions: Our results support the use of the James' Place Model for men in suicidal distress to aid in potentially preventing suicides in this high-risk group of the population. Highlights: Evaluates a brief psychological clinical intervention delivered in the community. Model effectively reduces suicide risk and findings can inform future services. Accessed men receiving an innovative intervention at the time of suicidal crisis.